2009
DOI: 10.1002/prca.200800158
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Helicobacter pylori biomarkers discriminative of low‐grade gastric MALT lymphoma and duodenal ulcer

Abstract: To date no reliable diagnostic method exists to predict, among the very large and clinically heterogeneous group of Helicobacter pylori-infected patients, the extremely small group at risk for developing low-grade gastric MALT lymphoma (LG-MALT). Search of proteomic biomarkers holds promise for the classification of the H. pylori strains with regard to this severe clinical outcome. In the present study 69 H. pylori strains isolated from patients with two different H. pylori-associated diseases, duodenal ulcer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Each gel slice was further divided into two equal parts each corresponding to one lane. The target protein was extracted from one of these slices by passive elution as described previously [25], and the mass of the passively eluted target protein was confirmed on gold arrays. The proteins in the corresponding second slice were subjected to trypsin digestion and LC-MS/MS microsequencing as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Each gel slice was further divided into two equal parts each corresponding to one lane. The target protein was extracted from one of these slices by passive elution as described previously [25], and the mass of the passively eluted target protein was confirmed on gold arrays. The proteins in the corresponding second slice were subjected to trypsin digestion and LC-MS/MS microsequencing as described below.…”
Section: Methodsmentioning
confidence: 99%
“…used another approach: surface‐enhanced laser desorption/ionisation time of flight (SELDI‐TOF) mass spectrometry to detect proteins specific for strains involved in specific diseases. They found an overexpression of a 50S ribosomal protein L7/L12 (13.2 kDa) in gastric MALT lymphoma and of a urease subunit (23.6 kDa) in peptic ulcer disease [37].…”
mentioning
confidence: 99%
“…RpL7/L12 was found both in the cytoplasm and membrane fractions (120,130). A recent study showed that RpL7/L12 is overexpressed in LG-MALT-associated strains when compared with DU-associated strains, suggesting that RpL7/L12 could be used as a biomarker for the differential diagnosis of H. pylori-associated clinical outcomes (17). RpL7/L12 was also reported previously to be overexpressed in gastric adenocarcinoma-associated strains (131).…”
Section: Cytosolic Protein Complexesmentioning
confidence: 64%
“…Several studies examined the proteome of strains associated with different pathologies (47,48,79,80,128,131,143,(152)(153)(154)(155), most of them based on immunoproteomics methods. However, only one of these studies included strains associated with LG-MALT (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation